Study on Immobilization of Formate Dehydrogenase on Polyethyleneimine Modified Carriers for the Enhancement of Catalytic Performance - Guo, Meng Ya; Zhai, Ting Ting; Wang, Cai Hong; Meng, Zi Hui; Fang Liu, Wen (Challenges and Advances in Chemical Science Vol. 8, 2022)
CO2 hydrogenation represents one important application way that not only removes CO2 from the atmosphere, but also generates high value-added chemicals. In the field of CO2 adsorption, polyethyleneimine (PEI) is a popular modifier, however it's rarely utilised in the immobilisation of enzymes that catalyse CO2 conversion. In this study, formate dehydrogenase (FDH) was immobilised on the surface of PEI-modified polyethylene membranes or silica microspheres and then used in the CO2 to formate process. The catalytic performance of immobilised FDH was 4.3 and 7.4 times that of free enzyme after optimising the immobilisation settings, owing to the carrier's promoting impact. FDH linked to polydopamine/PEI-SiO2 has higher activity and stability than biocatalytic membrane.